Increasing N deposition impacts neither diversity nor functions of deadwood‐inhabiting fungal communities, but adaptation and functional redundancy ensure ecosystem function. (6th April 2018) - Purahong, Witoon; Wubet, Tesfaye; Kahl, Tiemo; Arnstadt, Tobias; Hoppe, Björn; Lentendu, Guillaume; Baber, Kristin; Rose, Tyler; Kellner, Harald; Hofrichter, Martin; Bauhus, Jürgen; Krüger, Dirk; et al.
Summary: Nitrogen deposition can strongly affect biodiversity, but its specific effects on terrestrial microbial communities and their roles for ecosystem functions and processes are still unclear. Here, we investigated the impacts of N deposition on wood‐inhabiting fungi (WIF) and their related ecological functions and processes in a highly N‐limited deadwood habitat. Based on high‐throughput sequencing, enzymatic activity assay and measurements of wood decomposition rates, we show that N addition has no significant effect on the overall WIF community composition or on related ecosystem functions and processes in this habitat. Nevertheless, we detected several switches in presence/absence (gain/loss) of wood‐inhabiting fungal OTUs due to the effect of N addition. The responses of WIF differed from previous studies carried out with fungi living in soil and leaf‐litter, which represent less N‐limited fungal habitats. Our results suggest that adaptation at different levels of organization and functional redundancy may explain this buffered response and the resistant microbial‐mediated ecosystem function and processes against N deposition in highly N‐limited habitats.